The Role of ESG Component in Shaping Corporate Cost of Debt and Cost of Equity in Indonesia - Hanna Pramadhia, Jasmine; Anny Nainggolan, Yunieta (DINASTI RESEARCH, 2025)
This study aims to analyze how the ESG combined score and its components affect the cost of debt and equity for listed companies in Indonesia. Otoritas Jasa Keuangan (OJK) has issued regulations to encourage the inclusion of companies' ESG performance in investment decisions. This has resulted in companies getting incentives to improve their ESG performance. However, the actual impact of lower capital costs due to improved ESG performance is still unavailable in Indonesia. This study attempts to fill this gap by considering the impact of the assessment of the components that underlie ESG values: emission reduction, resource use, environmental innovation, workforce, community, human rights, product responsibility, CSR strategy, management, and shareholder rights on the cost of debt and equity. The results show the ESG combined score has no impact on the cost of debt. However, components such as emissions, environmental innovation, and human rights can directly affect the company's debt cost. In addition, the results show that the combined ESG score and almost all components that build the ESG score affect the company's equity cost. However, this study found that the majority had a positive relationship with heavy-polluting companies and a negative relationship with non-heavy-polluting companies.